Analisis Kesehatan Bank Perkreditan Rakyat (BPR) Gunung Arjuna Malang Menggunakan Metode CAMELS - Rahayu Widayanti (Akutansi Bisnis & Manajemen ( ABM ), 2015)
Bank rating is qualitatif and quantitative assessment of various aspects affecting the condition or performance of a bank to create a banking system that is healthy and able to compete nationally, improve customer protection, support the development of micro, small and medium enterprises (SMEs), as well as other provisions that are institutional and prudential. This study aims to determine the level of health of Bank Perkreditan Rakyat (BPR) Gunung Arjuna Malang with Camels approach. Secondary data collection using the financial statements. BPR Gunung Arjuna, published in 2011-2013. The analysis showed that the CAR above 20 % which shows that the capital position of banks are in good ranking, which means that the adequacy, composition, and projected capital in the Bank's troubled assets is a good cover. Although the CAR above 20%, when seen from the asset quality and management, the bank is at the optimum level yet, so it needs to improve the quality of public management and risk management, as well as the need to evaluate compliance with applicable regulations and commitment to Bank Indonesia or other parties. In terms of the ability to generate profits for shareholders or earnings, liquidity and sensitivity, the bank is in a position good enough, but needs an increase in operating profit, policy and liquidity management, as well as revamping the bank as a whole.